2003
DOI: 10.1093/jac/dkg384
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Sensititre YeastOne colorimetric antifungal panel and Etest with the NCCLS M38-A method to determine the activity of amphotericin B and itraconazole against clinical isolates of Aspergillus spp.

Abstract: The colorimetric method appears to be a suitable alternative procedure for antifungal susceptibility testing of Aspergillus spp. and is able to detect resistance to itraconazole. The range of MICs for amphotericin B by Etest is wider and for some strains is >16 mg/L, suggesting that this method could be useful for detecting resistant strains as occur in yeasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

10
48
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 20 publications
(16 reference statements)
10
48
1
Order By: Relevance
“…Practically no differences were observed among both microdilution methods; by the Sensititre method, all the strains were inhibited by 1 mg of drug/liter. This result is in concordance with previous studies using Sensititre with another azole antifungal agent, itraconazole (10,14).…”
supporting
confidence: 93%
See 4 more Smart Citations
“…Practically no differences were observed among both microdilution methods; by the Sensititre method, all the strains were inhibited by 1 mg of drug/liter. This result is in concordance with previous studies using Sensititre with another azole antifungal agent, itraconazole (10,14).…”
supporting
confidence: 93%
“…Overall, higher voriconazole MICs were obtained by the Sensititre method; similar results were obtained by Martín-Mazuelos et al (10) and Sánchez Sousa et al (14) with itraconazole. In contrast, Meletiadis et al (11) found that itraconazole MICs generated by Sensititre YeastOne were lower than those generated by the NCCLS method.…”
supporting
confidence: 87%
See 3 more Smart Citations